191k views
3 votes
Solve 4(t + 1) = 6t -1​

User ChaoS Adm
by
5.5k points

2 Answers

3 votes

Answer:

t=5/2

Explanation:

4(t + 1) = 6t -1​

=>4t+4=6t-1

=>6t-4t=4+1

=>2t=5

=>t=5/2

User Singhakash
by
4.5k points
3 votes

4(t + 1) = 6t -1​

Multiply the bracket by 4

4(t)+4(+1)=6t-1

4t+4=6t-1

Move +6t to the other side. Sign changes from +6t to -6t.

4t-6t+4=6t-6t-1

-2t+4=-1

Move +4 to the other side. Sign changes from +4 to -4.

-2t+4-4=-1-4

-2t=-5

Divide by -2

-2t/-2=-5/-2

Cross out -2 and -2, divide by -2 and then becomes t.

t=5/2 or t= 2 1/2 or t=2.5

Answer: t=5/2, t=2 1/2, t=2.5

User Porjaz
by
5.7k points